Assessing Trends in Tobacco Cessation in Diverse Patient Populations. Issue 3 (28th April 2015) - Stevens, Victor J.; Solberg, Leif I.; Bailey, Steffani R.; Kurtz, Stephen E.; McBurnie, Mary Ann; Priest, Elisa L.; Puro, Jon E.; Williams, Rebecca J.; Fortmann, Stephen P.; Hazlehurst, Brian L.
Abstract : Introduction: This study examined change in tobacco use over 4 years among the general population of patients in six diverse health care organizations using electronic medical record data. Methods: The study cohort ( N = 34 393) included all patients age 18 years or older who were identified as smokers in 2007, and who then had at least one primary care visit in each of the following 4 years. Results: In the 4 years following 2007, this patient cohort had a median of 13 primary care visits, and 38.6% of the patients quit smoking at least once. At the end of the fourth follow-up year, 15.4% had stopped smoking for 1 year or more. Smokers were more likely to become long-term quitters if they were 65 or older ( OR = 1.32, 95% CI = [1.16, 1.49]), or had a diagnoses of cancer (1.26 [1.12, 1.41]), cardiovascular disease (1.22 [1.09, 1.37]), asthma (1.15 [1.06, 1.25]), or diabetes (1.17 [1.09, 1.27]). Characteristics associated with lower likelihood of becoming a long-term quitter were female gender (0.90 [0.84, 0.95]), black race (0.84 [0.75, 0.94]) and those identified as non-Hispanic (0.50 [0.43, 0.59]). Conclusions: Among smokers who regularly used these care systems, one in seven had achieved long-term cessation after 4 years. This study shows the practicality of using electronic medical records for monitoring patient smoking status over time. Similar methods could be used to assess tobacco use in any health care organization to evaluate the impact of environmental and organizational programs.